2015
DOI: 10.1002/ar.23154
|View full text |Cite
|
Sign up to set email alerts
|

A Rabbit Model of Acanthamoeba Keratitis That Better Reflects the Natural Human Infection

Abstract: Acanthamoeba species are ubiquitous, free-living protozoa that can invade the cornea and result in Acanthamoeba keratitis (AK), a painful progressive sight-threatening corneal disease. Disease progression in current animal models is too rapid to mimic AK in humans accurately. This study provides a novel method for establishing AK in rabbits and compared it with the conventional method with regard to pathogenesis and immune response in humans. The New Zealand white rabbits were randomly divided into two experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…in all epithelial and stromal layers of the cornea, as well as regional stromal necrosis. In addition, the infection may be accompanied by a local necrosis of stromal fibers [24,25]. In a patient with Acanthamoeba keratitis, Kato et al [26] observed polymorphonuclear leukocytes in the corneal stroma, an abscess in the granulomatous tissue of sclera near the ciliary body, and macrophages and lymphocytes surrounding blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…in all epithelial and stromal layers of the cornea, as well as regional stromal necrosis. In addition, the infection may be accompanied by a local necrosis of stromal fibers [24,25]. In a patient with Acanthamoeba keratitis, Kato et al [26] observed polymorphonuclear leukocytes in the corneal stroma, an abscess in the granulomatous tissue of sclera near the ciliary body, and macrophages and lymphocytes surrounding blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of amoeba trophozoites into the anterior chamber of the eye did not cause morphological changes in the retina or posterior chamber of the eye [28]. However, in another study, an injection of Acanthamoeba into the corneal stroma led to severe encephalitis in some animals [29].…”
Section: Discussionmentioning
confidence: 91%
“…mannose-binding lectin and secreted proteases) and host factors that mediate resistance to the protist (e.g. IL-17A) [ 15 17 ]. Acanthamoeba infections are treated with drug combinations (e.g.…”
Section: Introductionmentioning
confidence: 99%